1997
DOI: 10.1074/jbc.272.30.19067
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Binding Specificity of the Neutrophil-activating Protein of Helicobacter pylori

Abstract: The possible interaction of the neutrophil-activating protein of Helicobacter pylori with target cell glycoconjugates was investigated by the binding of 125 I-labeled recombinant protein to glycosphingolipids from human neutrophils in solid phase assays. Thereby, a distinct binding of the neutrophil-activating protein to four bands in the acid glycosphingolipid fraction from human neutrophils was detected, whereas no binding to the non-acid glycosphingolipids or polyglycosyl ceramides from these cells was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 42 publications
2
83
0
1
Order By: Relevance
“…Despite the lag imposed by the effector delivered by the type IV secretion system, bacteria bound to phagocytes via one or more adhesins (25)(26)(27)120) are nevertheless internalized and found in phagosomes (46,71,139). Remarkably, fewer than half of the internalized population of unopsonized H. pylori cells are destroyed (1).…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…Despite the lag imposed by the effector delivered by the type IV secretion system, bacteria bound to phagocytes via one or more adhesins (25)(26)(27)120) are nevertheless internalized and found in phagosomes (46,71,139). Remarkably, fewer than half of the internalized population of unopsonized H. pylori cells are destroyed (1).…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…The family members seem to be involved in aerotolerance (11), H 2 O 2 resistance (11,12,57), cold shock adaptation (58), starvation tolerance (12), iron storage (22), neutrophil activation (59,60), carbohydrate binding (61), and adhesion (62). The molecular determinants mediating these activities are largely unknown.…”
Section: Fig 8 Effects Of the Putative Ferroxidase Center Mutationsmentioning
confidence: 99%
“…H pylori neutrophilactivating protein (HP-NAP), a 150-kDa iron-binding protein, is a ball-shaped dodecamer formed by fourhelix bundled subunits with its sequence similar to that of bacterioferritins and DNA binding proteins [5,6] . It has been designated as a neutrophil-activating factor because it promotes the adherence of neutrophils to endothelial cells and stimulates production of reactive oxygen species (ROS) in neutrophils by activating nicotinamide adenine dinucleotide phosphate (NADPH) oxidase in plasma membrane [7][8][9][10][11] . Satin et al [12] demonstrated that the purified recombinant HP-NAP is chemotactic for human neutrophils and monocytes, induces surface expression of β2-integrin, which mediates endothelial transmigration, adhesion and accumulation of leucocytes at the site of H pylori infection.…”
Section: Introductionmentioning
confidence: 99%